Natural regeneration following wind disturbance increases the diversity of managed lowland forests in NE Poland. (28th August 2018) - Szwagrzyk, Jerzy; Gazda, Anna; Dobrowolska, Dorota; Chećko, Ewa; Zaremba, Jakub; Tomski, Andrzej
Abstract: Questions: Are there significant differences in the density and composition of natural regeneration among habitat types? Is the abundance of regeneration higher in patches more seriously damaged by a windstorm than in patches not affected by the wind? Is the species diversity of regeneration greater than the diversity of mature trees prior to disturbance? Location: Szast Protected Forest, NE Poland. Methods: Throughout the Szast P.F., 111 sample plots were distributed in a regular grid 13 years after a windstorm. In plots located in disturbed forests, we measured all the canopy trees and the 30 young individuals of each size class (seedlings, short saplings and tall saplings) closest to the plot centre. In non‐disturbed patches, we measured all trees within a plot of predefined radius. For statistical analyses of differences in the diversity between mature stands and young generation, we used the Kruskal–Wallis test followed by Dunn's multiple comparison test. The relationship between the canopy layer and the young generation of trees was analysed using Spearman's rank correlation and a classic negative binomial regression. Results: Natural regeneration was more abundant in the coniferous and mixed coniferous habitat types than in the mixed deciduous type. The density of young trees was negatively correlated with the basal area of the trees that survived the windstorm and was positively correlated with canopy tree mortality. After the windstorm, Pinus sylvestris lost more trees than the other species; Picea abies and Betula pendula slightly increased their share; and the species that benefited most from the disturbance was Quercus robur . In the coniferous habitat type, the species diversity of the young generation of trees was higher than the diversity of the canopy trees prior to the windstorm. Conclusions: Leaving wind‐disturbed areas to natural regeneration could be a viable option for converting coniferous plantations into more diverse and species‐rich stands. Abstract : We studied natural regeneration processes in a large windthrown area in a lowland forest. The density of young trees was positively correlated with the canopy tree mortality. Species diversity among the regeneration was higher than the diversity of the canopy trees before the windstorm. Pinus sylvestris was less abundant among the regeneration than in the mature stands, while Quercus robur benefited most from the disturbance.